Periodontal Health Status and Assessment of Osteocalcin levels in Saliva of Diabetic Patients and Systemically Healthy Persons (Comparative study) - Daily, Zina Ali; Mohammed, Ayser Najah (Journal of Baghdad College of Dentistry, 2017)
ABSTRACTBackground: Diabetes and periodontitis are complicated prolonged disorders through a recognized two-way association. There is elongated-conventional mark that hyperglycaemia in diabetes is affected on immune-inflammatory response and disturb the action of osteoclast and in balance bone turnover, which might rise the person vulnerability to the progress of prolonged periodontitis. Osteocalcin is one of the greatest plentiful matrix proteins originate in bones and produced absolutely there. Small osteocalcin crumbles are noticed in regions of bone remodeling and are in fact degradation products of the bone matrix, that is released outside cells into the Gingival Crevicular Fluid (GCF) and saliva after destruction of periodontal tissue during periodontitisMaterials and Methods: Eighty patients with Type2Diabetes Maleates (T2DM), males and females, were recruited for the study, with an age range of (30-50) years were divided into four groups, (20 subjects each): poorly controlled Type 2Diabetes Mellitus with chronic periodontitis group (CP+pT2DM ) and well controlled Type 2Diabetes Mellitus with chronic periodontitis group(CP+wT2M) , group of patients with only chronic periodontitis (CP )and control group with healthy periodontium and systemically healthy. From all subjects five ml of unstimulated whole salivary samples were collected, then, the samples were centrifuged and the supernatants were collected and kept frozen until the biochemical analysis to measure OC concentrations then clinical periodontal parameters (plaque index, gingival index, bleeding on probing, probing pocket depth and clinical attachment loss) were recorded for all subjects at four sites per tooth except for the third molars.Results: The results of this study revealed highly significant differences among all study and control groups for all the clinical periodontal parameters (plaque index, probing pocket depth, clinical attachment loss) ,and OC concentrations. Additionally patients had chronic periodontitis with poorly controlled Type 2Diabetes Mellitus(CP+pT2DM )demonstrated the highest median values of all clinical periodontal parameters and highest increase in levels of salivary OC followed by CP+wT2M group then CP and Control groups. The current study demonstrates the correlation between OC concentrations with each one of the clinical parameters.It revealed highly significant strong positive correlations with PLI, GI and BOP score 1, while highly significant strong negative correlations with PPD. Also, non-significant weak positive correlation existed with CAL in CP+pT2DM group. Also, high significant strong positive correlation with PLI, GI, BOP and CAL; while, non-significant weak positive correlation with PPD in CP+wT2M group . High-significant strong positive correlation with BOP and CAL, as well as, high significant moderate positive correlation with PPD and significant weak positive correlation with PLI, while non-significant weak positive correlation with GI existed in CP group .Finally, high significant moderate positive correlation with PLI and GI existed in the Control group.Conclusion: Patients with poor glycemic control had more severe periodontal tissue break down with increase in levels of OC than well controlled type 2 diabetic patients and non-diabetic patients all of them with chronic periodontitis. So, this biochemical marker may be useful of periodontal tissue destruction and allowed practitioners for early diagnosis, prognosis and efficient management of periodontal diseases and type 2 diabetes mellitus